Deteksi Jumlah Penghuni Pada Ruangan Berpintu Untuk Smart Home Berbasis Arduino dan Sensor PIR - Lintang Cahyaning Ratri; Hurriyatul Fitriyah; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Counting people coming in and out of the desired region automatically is very important in business, management and security. This research introduces Detection system of people in the room that has doors for smart home based arduino and PIR sensors. The benefits of the system are for management and security. In this research, the purpose is focused on counting the number of people in the room that has the doors automatically, so, the owner can see the number of people in each room in his house periodically. The use of PIR sensors aims for detects human presence without disturbing the privacy of the householders. So the sensor is very suitable for home / office automation. This system uses arduino nano type and NRF24L01 type microcontroller as a wireless device. The result shows that the system has 100% accuracy in calculating people automatically by 6 times entering-exiting of the room testing. This system can overcome if the object that goes into the room is a non-human object (cat). This system can count 2 people as 2 people that can be detected from the distance between people about 3,5 meters. In data transmission test, system can send data at a distance of about 35 meters in open space (without wall barrier) and about 4 meters in room with wall barrier